Characterization of fishing and importance of crustaceans in the perception of artisanal fishermen, southern Espírito Santo, Brazil - Braga, Adriane Araújo; Oliveira, Ana Carolina Machado de; Zappes, Camilah Antunes (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
The traditional knowledge of fishermen about the biology and ecology of natural resources can play an important role in their preservation and conservation. The present study describes the importance of crustaceans based on the perception of artisanal fishers that work along the southern coast of the state of Espírito Santo state in south-eastern Brazil. The observations were made between September 2016 and February 2017, totalling 92 interviews. The fishermen are male, between 18 and 71 years old and with low education. For them, the decapod crustaceans are of ecological importance, as they form part of the food chain and the ecosystem, as well as being commercialized, used for proper consumption, and serving as bait. Fishermen consider the closed season, in which fishery is forbidden, important but incorrect for the region. The results demonstrate the importance of ethno-ecological studies to understand the perception of local players who work in artisanal fishing and thereby to facilitate the dialogue between managers and fishing communities.
Keywords: Traditional knowledge; Crab fishery; Southeastern Brazil